في هلاك الدور اليرقي وحياتية الدور العذري لحشرة ذبابة التدويد Capparis spinosa والشفلح Lawsonia inermis تقييم كفاءة المستخلص الميثانولي لنبات الحناء - ناظم الثامري علاء; عبد علي المنصور ناصر (University of Thi-Qar Journal of Science, 2011)
This present study was carried out to evaluate the effects of methanolic extracts for Lawsonia inermis and Capparis spinosa on the mortality of larval stage and biology of pupae of Chrysomya albiceps on the attempt to find out the best control.Methanolic extract of L. inermis gave the best mortality rate with 90% , 73.3% and 63.3% for the first larval instar in the 50% concetration , while the extract of C. spinosa was recorded 76.6% , 56.6% and 46.6% , 65.8% , the results also showed that the first larval instar was the highest effective with L. inermis and C. spinosa extracts as mortality rates reached 51.1% and 42.1% respectively , while the third larval instar was lowest with 20% and 32.1% respectively .The results also showed that pupae produced from comon larva a treated with both extracts were abnormal shapes and low weights ,and produce some deforming adults , the methanolic extract of was C. spinosa more effective with less rate of the weights0.103 gm/10 pupa while of L. inermis with 0.122gm/10 in the concentration 50% compared with control whose their average weight was 0.560 gm/10 , the extract of C. spinosa was recorded highest ratio for abnormal pupa with 100% in the 50% conce. while L. inermis with 96.6% .